2014
DOI: 10.1212/wnl.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported memory complaints

Abstract: Objective: We assessed salience of subjective memory complaints (SMCs) by older individuals as a predictor of subsequent cognitive impairment while accounting for risk factors and eventual neuropathologies.Methods: Subjects (n 5 531) enrolled while cognitively intact at the University of Kentucky were asked annually if they perceived changes in memory since their last visit. A multistate model estimated when transition to impairment occurred while adjusting for intervening death. Risk factors affecting the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
122
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 35 publications
13
122
0
1
Order By: Relevance
“…The present study shows that subjective deficits of everyday memory are more evident in elderly subjects with high plasma levels of Ab 1e42 , who also exhibited a thinner right temporal lobe than the low Ab 1e42 group. Recent evidence has shown that cognitively intact older individuals with subjective memory complaints presented increased AD-type brain pathology in regions of the medial temporal lobe (Kryscio et al, 2014), reductions of gray matter density in medial temporal regions similar to mild cognitive impairment (MCI) patients (Saykin et al, 2006), and aberrant patterns of functional connectivity in resting-state cortical networks (Hafkemeijer et al, 2013). Our study is the first to show that high plasma Ab 1e42 levels are associated with worse perception of everyday memory and thinner temporal cortex, suggesting that self-reported mnemonics in older adults with increased plasma Ab 1e42 levels may be helpful at identifying persons for clinical monitoring who might benefit from earlier therapeutic opportunities.…”
Section: Cognitive Functioning and Plasma Ab Levels In The Elderlymentioning
confidence: 99%
“…The present study shows that subjective deficits of everyday memory are more evident in elderly subjects with high plasma levels of Ab 1e42 , who also exhibited a thinner right temporal lobe than the low Ab 1e42 group. Recent evidence has shown that cognitively intact older individuals with subjective memory complaints presented increased AD-type brain pathology in regions of the medial temporal lobe (Kryscio et al, 2014), reductions of gray matter density in medial temporal regions similar to mild cognitive impairment (MCI) patients (Saykin et al, 2006), and aberrant patterns of functional connectivity in resting-state cortical networks (Hafkemeijer et al, 2013). Our study is the first to show that high plasma Ab 1e42 levels are associated with worse perception of everyday memory and thinner temporal cortex, suggesting that self-reported mnemonics in older adults with increased plasma Ab 1e42 levels may be helpful at identifying persons for clinical monitoring who might benefit from earlier therapeutic opportunities.…”
Section: Cognitive Functioning and Plasma Ab Levels In The Elderlymentioning
confidence: 99%
“…For example, a recent study among cognitively intact older adults demonstrated that subjective memory complaints were associated with increased risk of cognitive impairment and Alzheimer-type brain pathology [1]. Subjective cognitive complaints may be particularly prevalent among older adults with epilepsy (OAE) given that this group demonstrates objective cognitive deficits and is at risk for cognitive impairment, particularly for memory tests, compared to older adults without epilepsy [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Though multifactorial, AD Worry does not seem to be associated with objective cognitive impairment. SCD is widely considered to be associated with future cognitive impairment and is therefore used as a screening tool for detecting preclinical stages of dementia [1,[26][27][28][29]. Our finding of a higher frequency of SCD+Worry in controls with AD Worry compared to those without AD Worry indicates that AD Worry could be an early indicator of future cognitive impairment.…”
Section: Discussionmentioning
confidence: 62%